Growth kinetics and validation of near‐physiologically synchronized HEK293S Cultures. Issue 5 (22nd April 2015) - Castillo Salvador, Alan Eduardo; Fuge, Grischa; Jandt, Uwe; Zeng, An‐Ping
<x xml:space="preserve">Abstract</x> For investigation of cell cycle‐specific processes in cell cultures, synchronization methods can be applied, especially when single‐cell analytics are not applicable. Thorough validation is essential to minimize distortions introduced by the synchronization procedure and to derive valid data, which is often neglected. In this study, synchronization has been performed and validated for the first time on a human producer cell line (HEK293S) using counterflow centrifugal elutriation. Two main fractions were obtained, with the amount of G2/M cells reduced to ∼5% in the first fraction, compared to ∼16% in the non‐synchronized state, and enriched to ∼30% in the second fraction. Special care was taken with respect to the extraordinary sensitivity of these cells. Validation of correctness and degree of synchronization were based on DNA content, growth behavior, cell size distribution and consumption and production rates. The resulting cell cycle distributions, effective growth rates, and characteristic cell diameter oscillated concertedly for up to 100 h. To facilitate analysis, a new and simple approach to estimate the cell cycle position is introduced and validated. It shows that after a recovery time of 18–24 h, all relevant properties return to the state of non‐synchronized cultures. This indicates that cell cycle specific analysis can only be valid starting from approximately 18–24 h after synchronization.